The Comparison Study of Flexible Ureteroscopic Suctioning Lithotripsy With Intelligent Pressure Control Versus Minimally Invasive Percutaneous Suctioning Nephrolithotomy in Treating Renal Calculi of 2 to 3 cm in Size. (October 2019) - Chen, Hua; Qiu, Xuanxi; Du, Chuance; Xie, Donghua; Liu, Tairong; Wang, Gongxian; Song, Leming
Purpose . To compare the efficacy and safety of flexible ureteroscopic suctioning lithotripsy (FURS) using patented designed intelligent irrigation and suctioning intraluminal pressure-control platform and integrated pressure-measuring suctioning ureteral access sheath versus minimally invasive suctioning percutaneous nephrolithotomy (MPCNL) in treating renal calculi at 2 to 3 cm in size. Methods . Ninety-one patients who met the criteria were included in the study. Among these, 46 patients underwent transurethral flexible ureteroscopic lithotripsy and the other 45 patients underwent MPCNL. We retrospectively analyzed the clinical data for the 2 groups and parameters including stone clearance rate, complication rate, average operative time, average postoperative hospitalization duration, and average postoperative hemoglobin level decrease were compared. Results . The hospitalization time for the FURS group was 3.53 ± 1.25 days, which was statistically shorter than that of the MPCNL group, which was 6.54 ± 2.36 days. There was significantly more patients needing pain medication postoperatively in the MPCNL group with statistical difference between the 2 groups ( P = .015). Also, there was more significant hemoglobin level drop in the MPCNL group with statistical difference between the 2 groups. However, there were no statistical differences between the 2 groups on average operative time and stone clearance rate. Conclusion . Both the operative methods are safe and efficacious in treating solitary renal calculus at 2 to 3 cm in size. However, FURS has more advantages including shorter hospital stay, less complication, and less bleeding.